COMPARATIVE INVESTIGATION OF TOTAL ANTIOXIDANT AND FREE RADICAL SCAVENGING ACTIVITIES OF TWO ALLIUM SPECIES - Thampi, Nivetha; Jeyadoss, Veronica Shalini (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The main intention of this study was to assess the comparative free radical scavenging and total antioxidant capacities (TAC) of fresh Allium sativum (garlic) bulbs and Allium cepa cultivar (green onion) leaves and bulbs for aqueous and methanolic extracts. Methods: The antioxidant ability of the different plant extracts were assessed using TAC method as well as hydrogen peroxide (H2O2) free radical scavenging method. Results: H2O2 free radical scavenging assay showed that the methanolic extracts of garlic bulbs, green onions leaves, and green onion bulbs produced a maximum percentage scavenging of 89%, 85.4%, and 66.4% respectively at 1000 Î¼g/ml. The methanolic extract of garlic showed the minimum value for 50% inhibitory concentration (IC50) of 257.54 Î¼g/ml followed by the aqueous extract of green onion leaves with IC50 of 258.33 Î¼g/ml. TAC revealed that garlic bulbs and green onions leaves exhibited high percentage antioxidant capacity of 91.66% and 91.21% respectively at 1000 Î¼g/ml. The minimum IC50 values for methanolic extracts of garlic and green onion leaves were found to be 64.033 Î¼g/ml and 69.965 Î¼g/ml respectively. The IC50 value for ascorbic acid was found to be 88.321 Î¼g/ml. Conclusion: Based on this aspect, we propose that this investigation can lead to the establishment of new and more potent drugs from cheaper native plants from natural origin since lacunae still remain in scrutinizing the various cultivars of green onions. Further studies are recommended for the in vivo investigations to commercialize their use as a cure to cancer. Keywords: Green onion, Garlic, Total antioxidants capacity, Hydrogen peroxide free radical scavenging assay, Free radicals, Cancer.